Environmental Analysis of Organic Pollutants - Liu, Wenbin (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
In recent decades, the environmental impact of organic pollutants, especially persistent and emerging organic pollutants, has attracted widespread attention, and related research has been rapidly developed. Organic pollutants represent a popular topic of research in the environmental field. Large amounts of organic pollutants, which are widely distributed in air, water, sediment, soil, and other environmental media, are created via industrial production and other human activities. A series of research projects have been carried out regarding the development of analytical methods for organic pollutants, the distribution of environmental media, environmental concentration, environmental fate, the exploration of new pollutants, and the non-target analysis of organic pollutants.